Law as a ‘discovery of being’: the Minos in the light of the Cratylus - Edoardo Benati (Études Platoniciennes, 2021)
In this paper I propose to verify the hypothesis that (some of) the Pseudoplatonica seek to elucidate key Platonic themes by reframing philosophical issues already present in the genuine dialogues. To do this, I consider the argumentative strategies of the first section of the Minos (313a1-317d2), and I argue that one can trace here the same tension between naturalism and conventionalism that is at play in Plato’s Cratylus. The strategies that both texts employ in order to reconcile this ‘struggle’ appear to be philosophically grounded in what I will be calling mild naturalism.